2012
DOI: 10.1007/s00220-012-1643-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Density of Eigenvalue Clusters for the Perturbed Landau Hamiltonian

Abstract: We consider the Landau Hamiltonian (i.e. the 2D Schrödinger operator with constant magnetic field) perturbed by an electric potential V which decays sufficiently fast at infinity. The spectrum of the perturbed Hamiltonian consists of clusters of eigenvalues which accumulate to the Landau levels. Applying a suitable version of the anti-Wick quantization, we investigate the asymptotic distribution of the eigenvalues within a given cluster as the number of the cluster tends to infinity. We obtain an explicit desc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…• As already mentioned, in [19] it was supposed that V satisfies (1.1) with ρ > 1. Then the Radon transform…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• As already mentioned, in [19] it was supposed that V satisfies (1.1) with ρ > 1. Then the Radon transform…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in [19] it was shown that if V satisfies ) as q → ∞. Moreover, in [19] the asymptotic density of the eigenvalue clusters was studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their perturbations have been investigated in [35,44], and the asymptotic behaviour of the eigenvalues was analysed in [37,40,41,[48][49][50]57]. The results of this paper apply for the Cauchy problem (1.1) for the operator L from (3.2).…”
Section: Landau Hamiltonian In 2dmentioning
confidence: 99%
“…Much of the inspiration for both the content of this paper and the proofs may be found in [7], where similar asymptotics are determined for the spectrum of the Landau Hamiltonian (i.e. two-dimensional Schrödinger operator with a constant homogeneous magnetic field) perturbed by a potential which obeys the same condition (1.2).…”
Section: 3mentioning
confidence: 99%